Forensic Engineering 2022 - Elevating Forensic Engineering - Liu, Rui; Mulea, Carmen C; Parfitt, M. Kevin; Cavalline, Tara L (American Society of Civil Engineers (ASCE), 2022)
Selected papers from the Ninth Congress on Forensic Engineering, held in Denver, Colorado, November 4-7, 2022. Sponsored by the Forensic Engineering Division of ASCE. This collection contains 122 peer-reviewed papers on a wide variety of forensic engineering subjects. Topics include: building enclosures, including roofs, façades, and foundations; infrastructure performance; natural disasters and extreme conditions; technologies for forensic investigations; forensic engineering education; construction performance and safety; analysis, design, repairs, and remediation; material performance; and professional practice in forensic engineering. This proceedings will be of interest to forensic engineering practitioners, project and construction managers, architects, researchers, and designers to advance their understanding of performance failures and state-of-the-art investigative tools and procedures.